PENGARUH MOTIVASI, KEPRIBADIAN DAN PENGETAHUAN BERWIRAUSAHA TERHADAP MINAT BERWIRAUSAHA MASYARAKAT DI WILAYAH DESA SEBATU KECAMATAN TEGALLALANG - Tjokorda Gde Agung Wijaya Kesuma Suryawan; I Wayan Cita Wardita (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
There is attention and there are problems related to Motivation, Personalityand Knowledge of Entrepreneurship in an effort to increase interest inentrepreneurship in the Sebatu Village community, especially among youngpeople and people who have been laid off due to the impact of Covid-19 in their place of work, so this research is very feasible. further investigated theinfluence of motivation, personality and knowledge of entrepreneurship inthe community of Sebatu Village, Tegallalang District, Gianyar Regency.The purpose of the study was to determine the effect of SimultaneousMotivation, Personality and Entrepreneurial Knowledge on EntrepreneurialInterest in the Sebatu Village community, to determine the partial effect ofMotivation on Entrepreneurial Interest in the Sebatu Village community, todetermine the partial influence of Personality on Entrepreneurial Interest inthe local community. Sebatu Village, to determine the effect ofEntrepreneurial Knowledge partially on Entrepreneurial Interest in thepeople of the Sebatu Village area. The data were analyzed by using thevalidity and reliability test of the research instrument, data description,classical assumption test, normality test, multicollinearity test,heteroscedasticity test, multiple linear regression analysis, coefficient ofdetermination analysis, partial significant test (t-test), F test. The resultsshowed there is a positive and significant influence partially orsimultaneously between motivation, personality and knowledge ofentrepreneurship on the community's entrepreneurial interest in the Sebatuvillage area, Tegallalang sub-district.